Аналіз змін показників якості ізоляції високовольтних вводів протягом тривалої експлуатації - Загайнова, Олександра Анатоліївна; Сердюкова, Галина Миколаївна (НТУ "ХПІ", 2017)
Виконаний аналіз особливостей змін характеристик якості ізоляції конденсаторного типу високовольтних вводів протягом тривалої експлуатації. Показано, що швидкість зміни значень показників якості змінюється на різних проміжках часу. Інтенсивність процесів старіння ізоляції залежить від умов експлуатації високовольтних вводів. Отримані результати дозволяють оптимізувати математичні моделі прийняття рішень при оцінці стану високовольтних вводів, за рахунок обліку наявності зв'язків між показниками діелектричних характеристик внутрішньої ізоляції вводів силових трансформаторів. Виконано перевірку відхилення від лінійності часових рядів для діелектричних показників якості ізоляції високовольтних вводів.

The results of periodic measurements of quality indicators of condenser type insulation high-voltage bushings considered as a time series containing information about changing the value of this indicator since the installation of inputs and the current moment. The task of forming an array of statistically homogeneous time series reduces to finding a combination of time series of indicators that would provide the maximum value of the correlation ratio for a given time interval. For the formation of groups of bushings with the same drift velocity indicators of quality insulation used criterion of maximum empirical correlation ratio. It was formed several data sets for each indicator of quality insulation, for which as a result of the testing was find the maximum value of the correlation ratio. To evaluate the effectiveness of the performing procedure statistically homogeneous time series analysis was performed tightness stochastic association between indicators of the quality of the bushings insulation and time of exploitation. It was found that under conditions of continuous operation, the aging of the high-voltage inputs isolation takes place at different speed.
Analysis of changes in insulation quality indicators of high-voltage bushings of during long-term operation
Keywords: однорідний часовий ряд; кореляційне відношення; дисперсійний аналіз; відхилення від лінійності; time series; correlation ratio; analysis of variance